2011
DOI: 10.1177/0145482x1110500702
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Write in Braille: An Analysis of Writing Samples from Participants in the Alphabetic Braille and Contracted (ABC) Braille Study

Abstract: This article reports the results of data from 114 writing samples of 39 children who read braille and who were included in the Alphabetic Braille and Contracted Braille (ABC) Study between 2002 and 2005. Writing characteristics, miscues, and composition characteristics are analyzed, and two case studies are included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 4 publications
0
8
0
11
Order By: Relevance
“…During the drafting stage, authors must choose precise words to convey ideas and content while maintaining focus on conventions of English such as spelling and grammar. Conventions are considered to be a strength for children who are visually impaired (Erin & Wright, 2011;Wall Emerson, Holbrook, & D'Andrea, 2009;Wall Emerson, Sitar, Erin, Wormsley, & Herlich, 2009). In polished writing samples words and sentences connect ideas smoothly, allowing the reader to move fluidly through the composition to understand the author's intended meaning (Lenski & Johns, 2010).…”
mentioning
confidence: 99%
“…During the drafting stage, authors must choose precise words to convey ideas and content while maintaining focus on conventions of English such as spelling and grammar. Conventions are considered to be a strength for children who are visually impaired (Erin & Wright, 2011;Wall Emerson, Holbrook, & D'Andrea, 2009;Wall Emerson, Sitar, Erin, Wormsley, & Herlich, 2009). In polished writing samples words and sentences connect ideas smoothly, allowing the reader to move fluidly through the composition to understand the author's intended meaning (Lenski & Johns, 2010).…”
mentioning
confidence: 99%
“…In the course of the Alphabetic Braille and Contracted (ABC) Braille Study carried out in 2002–2007 in 15 states of the United States and one province of Canada, it became clear that students with visual impairments had difficulties in building up a reading vocabulary in comparison to sighted children (Emerson et al, 2009). Writing skills analyses showed that most writing errors were of a general nature and only about 13% could be described as ‘Braille-specific’ (e.g., missing dots, dot confusion; Erin & Wright, 2011). With regard to Braille reading, there is a broad consensus that, in analogy to visual reading, larger units of perception can be formed than individual letters, since in both writing systems alphabetic words are recognised faster than non-alphabetic words (Millar, 1997) and frequent used words are easier to read than rare ones (Carreiras & Alvarez, 1999; Hughes, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The most comprehensive peer-reviewed study of the writing of children with visual impairments was conducted as part of the Alphabetic Braille and Contracted Braille Study (Erin & Wright, 2011). Researchers in this study analyzed writing samples from 39 students who were blind or functionally blind, and who used braille for writing, and scored writing quality for 29 students based on (1) content, (2) structure, and (3) voice, style, and tone.…”
mentioning
confidence: 99%
“…Although there is a growing body of research on the development of literacy skills for children with visual impairments, not much is known about their writing. Writing research is often limited to subgroups, such as braille users (e.g., Erin & Wright, 2011), or subskills, such as handwriting (e.g., Harris-Brown, Richmond, Della Maddalena, & Jaworski, 2015; Plimmer, Reid, Blagojevic, Crossan, & Brewster, 2011), or spelling (e.g., Argyropoulos & Martos, 2006; Clark-Bischke & Stoner, 2009). Lacking in the research are examinations of (a) the writing skills of a more comprehensive set of students with visual impairments (i.e., students who are blind only, students with low vision only, and students with visual impairments and additional disabilities) and (b) more global measures of their writing skills (e.g., writing quality).…”
mentioning
confidence: 99%